Lesão complexa da via biliar principal: a ligadura como opção associada a colecistojejunostomia - Starling,Sizenando Vieira (2003)
The authors present a case of distal common bile duct injury. Ligation of the bile duct and a bypass cholecystojejunostomy were chosen as treatment. Diagnosis of blunt traumatic injury to the extrahepatic biliary ducts may be difficult due to the benign nature of initial bile peritonitis. Surgical treatment for associated abdominal injuries usually makes the diagnosis possible. One of the challenges in the treatment of these injuries relates to the small diameter of the, usually, normal common bile duct. Primary repair and T tube drainage is the best option for non-complex injuries. End-to-end anastomosis and, preferentially, biliary-enteric anastomosis are the best surgical options for more complex injuries. Severe injuries have high complication rates, especially when the distal portion of the common bile duct is affected. Early leaks and late strictures are likely to develop in these situations. Cholecistojejunostomy and ligation of the injuried common bile duct are good surgical options for complex injuries. They carry a low complication rate and consequently low morbidity.